Morphological Spectrum of Salivary Gland Tumours - Nayak, Dr. Rakshatha; Dr. Ramadas Naik, Dr. Prema Saldanha, Dr. Krishnaraj Upadhyaya (International Journal of Innovative Research in Medical Science, 2017)
Background: Salivary gland tumours consist of heterogeneous lesions with complex and diverse characteristics and distinct biological behaviour. Histopathology is one of the most valuable means of diagnosis in salivary gland tumours. Methods: This retrospective study comprised of cases selected from the archives of the Department of Pathology. Patient’s demographic details were obtained from the records. The sections for histopathology were prepared from formalin-fixed paraffin-embedded tissues and stained with Haematoxylin and Eosin. Results: Out of thirty one cases of salivary gland specimens, twenty five cases were diagnosed as benign and six cases were malignant. Pleomorphic adenoma was the commonest benign tumour (61.4%). Mucoepidermoid carcinoma was the commonest malignant tumour (13%). Among the benign tumours, three cases of Warthin tumour and one case each of Oncocytoma and Intraductal papilloma were found. Among the malignant tumours, one case each of Acinic cell carcinoma, Clear cell carcinoma and Adenoid cystic carcinoma were found. Conclusion: Histopathological examination plays an important role in the diagnosis of salivary gland lesions. It helps to predict the prognosis by histological typing and the staging and grading of malignant neoplasms.